PPARγ Activates Autophagy by Suppressing the PI3K–AKT1–FOXO3 Signaling Pathway and thus Alleviates Hepatic Ischemia-Reperfusion Injury - Liu, Xinyu; Cui, Hengguan; Song, Xianqing; Shen, Weixing; Yan, Bin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatic ischemia-reperfusion injury (HIRI) refers to the damage caused by metabolic imbalance post-ischemia upon reperfusion, often occurring in scenarios like hemorrhagic shock, liver resection, and liver transplantation. Due to the complex nature of the mechanisms underlying metabolic imbalance, specific treatment options are lacking. Peroxisome proliferator activated receptor gamma (PPARγ) is a group of metabolic regulatory receptors that can influence HIRI by regulating autophagy, although the precise mechanism remains contentious. Materials and Methods: In vivo and in vitro experiments were conducted to simulate hypoxic conditions, evaluating the effects of PPARγ overexpression plasmids, autophagy inhibitors, phosphatidylinositol 3-kinase (PI3K) activators, and PPARγ agonists on HIRI. The activa tion status of the PI3K–AKT1–FOXO3 signaling pathway, autophagy levels, inflammatory responses, and liver cell/organ damage were analyzed using western blot, ELISA, flow cytometry, H&E staining, and TUNEL experiments. Results: Peroxisome proliferator activated receptor gamma can mitigate cell damage caused by hypoxia by activating autophagy, with the activation of autophagy being associated with the inhibition of the PI3K–AKT1–FOXO3 signaling pathway. Additionally, pretreatment of mice with the PPARγ agonist rosiglitazone can alleviate HIRI induced by ischemia by inhibiting the activation of the PI3K–AKT1–FOXO3 signaling pathway to induce autophagy. Conclusion: Peroxisome proliferator activated receptor gamma inhibited the PI3K-AKT1 FOXO3 signaling pathway, which in turn activated autophagy to alleviate HIRI. Cite this article as: Liu X, Cui H, Song X, Shen W, Yan B. PPARγ activates autophagy by suppressing the PI3K–AKT1–FOXO3 signaling pathway and thus alleviates hepatic ischemia-reperfusion injury. Turk J Gastroenterol. 2025;36(10):649-657